Predicting the Acceptance of Metaverse for Educational Purposes in Universities: A Structural Equation Model and Mediation Analysis of the Extended Technology Acceptance Model - Rosli, Mohd Shafe; Saleh, Nor Shela (2024)
This study investigated factors that predict the acceptance of metaverse applications for educational usage among university students from the facet of the Technology Acceptance Model. As both the metaverse and the Technology Acceptance Model gained popularity, little attention was paid to the metaverse’s acceptance and the factors that led to the metaverse’s acceptance from the Technology Acceptance Model’s tenets. This creates a gap in our existing understanding of the metaverse. To fll the gap, Future Learning Intention (FLI), Technology Optimism (TO), Hedonic Motivation (HM), Perceived Enjoyment (PE), Technology Trust (TT), and Anticipated Benefts (AB) were integrated into the Technology Acceptance Model as external variables to study the acceptance of the metaverse among university students. The extended Technology Acceptance Model consists of 18 hypotheses that were tested using the Structural Equation Model and Mediation Analysis with data from 215 university students. The model developed was found to accurately determine university students’ acceptance of metaverse applications. FLI and TT were signifcant predictors of usefulness, while FLI, TT, and AB were signifcant antecedents of ease of use, according to the model. The samples’ Attitudes Toward Using (AT) mediated the relationship between Perceived Usefulness (PU) and Perceived Ease of Use (PEU) toward the students’ Behavioural Intention (BI) to use the metaverse. Suggestions for educational practise and metaverse development were highlighted for the metaverse’s future development in both educational and non-educational contexts. Future development of metaverse applications should prioritise understanding their prospective users’ characteristics while still maintaining the applications’ usefulness and ease of use.